Recurring Nightmares and Silver Linings: Understanding How Past Abusive Supervision May Lead to Posttraumatic Stress and Posttraumatic Growth - Vogel, Ryan M.; Bolino, Mark C. (Academy of Management Review, 2020)
Research on traumatic events indicates that the effects of abuse can last a lifetime. This work further suggests that people who have been mistreated can grow and experience positive outcomes from traumatic experiences. We integrate theory on traumatic events, the self-concept, appraisal, and coping to develop a process model about the effects of abusive supervision after it has ended. According to our model, the more employees experience abusive supervision as extraordinary, uncontrollable, and overwhelming, the more likely they are to experience changes to the content of their self-concept, which leads to posttraumatic stress (PTS), a state characterized by alternating states of intrusive thoughts, avoidance, and hyperarousal. We propose that having a complex self-concept protects abused employees from experiencing PTS by diluting and segregating the impact of past abusive supervision. We also identify differences in cognitive processing regarding employees’ experience and appraisal of memories associated with past abuse, and argue that these differences determine whether abused employees recover from PTS, endure prolonged PTS, or experience posttraumatic growth (PTG). Finally, we explain how prolonged PTS and PTG resulting from past abusive supervision affect employees’ personal and professional lives in the future, thereby revealing a unique set of consequences for the abusive supervision literature.